2000
DOI: 10.1002/1520-7560(2000)9999:9999<::aid-dmrr155>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis in fibrocalculous pancreatic diabetes mellitus is not associated with common mutations in the trypsinogen gene

Abstract: These results indicate that chronic pancreatitis of FCPD is unlikely to be caused by common mutations in the trypsinogen gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…However, one of them performed a PCR-RFLP assay for the R122H mutation on 11 FCPD and five TCP patients only 20 and the other one analysed FCPD patients only. 21 In agreement with earlier reports, single C to T transitions in exon 4 (162Asp (GAC-GAT)) and exon 5 (246Asn (AAC-AAT)) without amino acid substitution were identified in the majority of patients (85%) as well as in normal controls (90%). [7][8][9] Sequence analysis of the SPINK1 gene Direct sequencing of the coding exonic and flanking intronic sequences including the promoter region of SPINK1 detected mutations in 32 out of 68 patients analysed.…”
Section: Sequence Analysis Of the Prss1 Genesupporting
confidence: 91%
See 1 more Smart Citation
“…However, one of them performed a PCR-RFLP assay for the R122H mutation on 11 FCPD and five TCP patients only 20 and the other one analysed FCPD patients only. 21 In agreement with earlier reports, single C to T transitions in exon 4 (162Asp (GAC-GAT)) and exon 5 (246Asn (AAC-AAT)) without amino acid substitution were identified in the majority of patients (85%) as well as in normal controls (90%). [7][8][9] Sequence analysis of the SPINK1 gene Direct sequencing of the coding exonic and flanking intronic sequences including the promoter region of SPINK1 detected mutations in 32 out of 68 patients analysed.…”
Section: Sequence Analysis Of the Prss1 Genesupporting
confidence: 91%
“…20 Subsequent extension of the study to include 50 South Indian and 70 Bangladeshi patients with FCPD excluded common mutations in exons 2 and 3 of the PRSS1 gene. 21 Ours is the first report where analysis of the whole coding sequence of the cationic trypsinogen gene does not show any causal mutation in TCP patients. Trypsin plays a central role in pancreatic exocrine physiology by acting as a trigger enzyme leading to activation of all other pancreatic zymogens.…”
Section: Discussionmentioning
confidence: 93%
“…Reddy and Prasad [23] showed that a loss-of-function mutation in the chymotrypsinogen C (CTRC) gene was associated with TCP, as were mutations in the cathepsin B (CTSB) gene; however, as shown earlier by Hassan et al [24], mutations in the anionic and cationic trypsinogen gene did not show significant association with TCP. Similarly, the T allele frequency of methylenetetrahydrofolate reductase (MTHFR) gene was found to be a significant risk factor for chronic pancreatitis, underlying its crucial role in folate metabolism [25].…”
Section: The Cassava Hypothesismentioning
confidence: 95%
“…Familial aggregations sug gest a genetic etiolog y for TCP. However, on screening known susceptibility factor, PRSS1, reported to be associated with HP and CP in Western populations, no association with TCP was found [35][36][37] . Instead, the inhibitor of trypsinogen called SPINK1 has been reported to be strongly associated with TCP [38,39] .…”
Section: Genetics Of Tcpmentioning
confidence: 99%